BUSINESS STRATEGY OPTIMIZATION: THE ROLE OF ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE - Denny Bernardus Kurnia Wahyudono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The Covid-19 pandemic has also had a lasting impact on performance in the fashion industry. Therefore, this study was made to understand the critical influence of entrepreneurial orientation and business strategy on business performance, especially when facing rapid environmental changes. This study took thirty-nine fashion business owners owned by Ciputra University, Surabaya students as census samples. The data results were then processed using the SEM-PLS method, SmartPLS software. The results show that entrepreneurial orientation can influence business strategy, and business strategy can influence business performance. The results of the mediating influence of business strategy show that it has yet to influence the relationship between entrepreneurial orientation and business performance.